Thermal performance of single-phase impingement - Tan, Kelvin Ting Song. (2011)
With the relentless trend of increasing power and decreasing dimensions of military embedded systems, the amounts of waste heat produce from the dense electronic assemblies is growing exponentially with no end in sight. Single phase jet impingement cooling offers high heat transfer coefficient capabilities and is considered as a viable solution to the above problem. In this work, thermal performance of single phase impingement cooling is investigated in aid to characterize for high gravitational acceleration environments. Experiments are carried out by means of nozzle plate having an array of 285 micro jets, at varying jet diameters of 0.5mm and 0.8mm, impinging on a surface area of 193cm2, at varying height of 3mm and 9mm setups, while encased in a chamber unit. Variation of the surface temperature over the heat source area and the average heat coefficient are reported at various flow rates ranging from 5LPM to 15LPM and power rating from 500W to 2kW respectively. Comparison of the heat transfer performance results among the various geometric parameters have demonstrated favourably for a smaller jet diameter and impingement height, as seen by the combination of 0.5mm jet orifice diameter with impingement height of 3mm, while impinging at high Reynolds flow regime considering the degradation in thermal performance seen at high acceleration levels.